Carbon fiber, preparation method thereof and composite material
By carbonizing and electrochemical oxidizing carbon fibers and sonicating them in a system containing tanninic acid and metal ions, the problem of insufficient bonding strength between carbon fibers and matrix resins is solved, and the interlayer shearing of composite materials is significantly improved Strength and mechanical properties.
Patent Information
- Application Number
- CN202411377130.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The interface bonding strength between carbon fiber and matrix resin in existing carbon fiber reinforced resin matrix composite materials needs to be further improved.
By carbonizing and electrochemical oxidizing the carbon fiber, oxygen-containing functional groups are introduced and ultrasonic treatment is carried out in a system containing tanninic acid and metal ions, the interface bonding strength between the carbon fiber and the matrix resin is improved.
The interface bonding strength between carbon fiber and matrix resin is significantly improved, the interlayer shear strength of the composite material is enhanced, and the mechanical properties of the material are improved.
Smart Images

Figure CN119221280A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon fiber preparation, and in particular to a carbon fiber and a preparation method thereof and a composite material. Background Art
[0002] Carbon fiber reinforced resin-based composite materials are composed of carbon fiber and matrix resin. They have many excellent physical and mechanical properties such as light weight, high strength, and conductivity. They are widely used in aviation, aerospace industry and various mechanical industries. They can largely replace traditional metal materials as main load-bearing and secondary load-bearing structural components, and improve the working efficiency and application scope of aerospace vehicles.
[0003] However, the interface bonding strength between carbon fibers and matrix resin in existing carbon fiber reinforced resin-based composite materials needs to be further improved. Summary of the invention
[0004] The purpose of the present application is to provide a carbon fiber and a preparation method thereof and a composite material, which are intended to improve the interface bonding strength between the carbon fiber and the matrix resin.
[0005] In a first aspect, the present application provides a method for preparing carbon fiber, the method comprising: electrochemically oxidizing a carbon fiber matrix after carbonization to obtain an intermediate; and ultrasonically treating a mixed system containing the intermediate and a treatment liquid, wherein the treatment liquid contains tannic acid and metal ions.
[0006] The present application sequentially performs carbonization treatment and electrochemical oxidation treatment on the carbon fiber matrix, so that more oxygen-containing functional groups can be introduced into the carbon fiber surface, which can improve the wettability and adhesion of the carbon fiber, so as to increase the interface bonding strength between the carbon fiber and the matrix resin. Furthermore, the present application performs ultrasonic treatment on the carbon fiber matrix after electrochemical oxidation treatment in a system containing tannic acid and metal ions, which can further increase the interface bonding strength between the obtained carbon fiber and the matrix resin.
[0007] In combination with the first aspect, in an optional embodiment of the present application, the total amount of electricity for electrochemical oxidation treatment is 20 to 120 C / g.
[0008] In the above technical solution, the prepared carbon fiber and the matrix resin can have a higher interface bonding strength.
[0009] Optionally, the electrochemical oxidation treatment time is 30 to 60 seconds.
[0010] In combination with the first aspect, in an optional embodiment of the present application, the electrochemical oxidation treatment adopts a multi-stage electrochemical oxidation treatment.
[0011] In the above technical solution, when the total amount of electricity in the electrochemical oxidation treatment is consistent, compared with the single-stage electrochemical oxidation treatment, the multi-stage electrochemical oxidation treatment can further improve the interface bonding strength between the prepared carbon fiber and the matrix resin.
[0012] Optionally, the number of stages of the multi-stage electrochemical oxidation treatment is 2, 3 or 4.
[0013] In combination with the first aspect, in an optional embodiment of the present application, the electrolyte for electrochemical oxidation treatment is selected from sodium hydroxide, sodium bicarbonate or sulfuric acid.
[0014] In the above technical solution, the electrolyte for electrochemical oxidation treatment is selected from the above substances, which can introduce more oxygen-containing functional groups on the surface of the carbon fiber, improve the wettability and adhesion of the carbon fiber, and thus increase the interface bonding strength between the carbon fiber and the matrix resin.
[0015] In combination with the first aspect, in an optional embodiment of the present application, the temperature of the carbonization treatment is 1200-1500°C.
[0016] In the above technical solution, the carbon fiber matrix can be fully carbonized, which is conducive to the introduction of more oxygen-containing functional groups on the surface of the carbon fiber after the subsequent electrochemical oxidation treatment.
[0017] Optionally, the carbonization treatment time is 40 to 100 seconds.
[0018] In combination with the first aspect, in an optional embodiment of the present application, the metal ions include Fe 3+ 、Na + , Cu 2+ and Zn 2+ At least one of; or / and, the solvent in the treatment liquid is water; or / and, the pH of the treatment liquid is 8-9.
[0019] In the above technical solution, the prepared carbon fiber and the matrix resin can have a higher interface bonding strength.
[0020] In combination with the first aspect, in an optional embodiment of the present application, the molar ratio of tannic acid to metal ions is (0.08-0.5):1.
[0021] Optionally, the mass concentration of tannic acid in the treatment solution is 0.5-5.0 mg / mL.
[0022] In combination with the first aspect, in an optional embodiment of the present application, the power of the ultrasonic treatment is 120-200W.
[0023] In the above technical solution, the prepared carbon fiber and the matrix resin can have a higher interface bonding strength.
[0024] Optionally, the ultrasonic treatment time is 30 to 60 minutes.
[0025] In a second aspect, the present application provides a carbon fiber, which is prepared by using any preparation method provided in the first aspect.
[0026] The carbon fiber provided in the present application has a high interface bonding strength with the matrix resin, which can improve the interlaminar shear strength of the composite material formed by the carbon fiber and the matrix resin.
[0027] In a third aspect, the present application provides a composite material, which includes a matrix resin and the carbon fiber provided in the second aspect.
[0028] The composite material provided in the present application has a high interface bonding strength between the carbon fibers and the matrix resin, and the composite material has a high interlaminar shear strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 A flow chart of the method for preparing carbon fiber provided in this application. DETAILED DESCRIPTION
[0031] The present application provides a method for preparing carbon fiber, which comprises: electrochemically oxidizing a carbon fiber matrix after carbonization to obtain an intermediate; and ultrasonically treating a mixed system containing the intermediate and a treatment liquid, wherein the treatment liquid contains tannic acid and metal ions.
[0032] The present application sequentially performs carbonization treatment and electrochemical oxidation treatment on the carbon fiber matrix, thereby introducing more oxygen-containing functional groups on the carbon fiber surface, improving the wettability and adhesion of the carbon fiber, and thus increasing the interface bonding strength between the carbon fiber and the matrix resin.
[0033] Furthermore, the present application performs ultrasonic treatment on the carbon fiber matrix after electrochemical oxidation treatment in a system containing tannic acid and metal ions. The conjugated structure of the benzene ring of tannic acid can form a π-π bond with the carbon fiber matrix, so that the surface of the carbon fiber matrix can be quickly covered with tannic acid molecules; the large amount of phenolic hydroxyl groups contained in tannic acid increase the surface activity of the carbon fiber, and the phenolic hydroxyl groups on the surface of the carbon fiber can react with the epoxy groups in the matrix resin to produce chemical bonds, thereby further improving the interface bonding strength between the prepared carbon fiber and the matrix resin.
[0034] Figure 1 For the process flow chart of the carbon fiber preparation method provided in this application, please refer to Figure 1 , the preparation method of carbon fiber comprises the following steps:
[0035] S110, electrochemically oxidizing the carbon fiber matrix after the carbonization treatment to obtain an intermediate.
[0036] In the present application, the carbon fiber substrate after carbonization treatment is used as an anode and placed in an electrolyte solution; through anode electrolysis, active oxygen is generated to oxidize the carbon fiber surface, so that more oxygen-containing functional groups are introduced into the carbon fiber surface.
[0037] In some optional embodiments of the present application, the total amount of electricity for electrochemical oxidation treatment is 20 to 120 C / g; so that the carbon fiber matrix has a more appropriate degree of oxidation, and the obtained carbon fiber and the matrix resin have a higher interface bonding strength. If the total amount of electricity for electrochemical oxidation treatment is low, the active groups on the surface of the carbon fiber will be reduced, and the interface bonding strength between the carbon fiber and the matrix resin will be slightly reduced; if the total amount of electricity for electrochemical oxidation treatment is high, the carbon fiber matrix will be over-oxidized, which will also cause the interface bonding strength between the carbon fiber and the matrix resin to be slightly reduced.
[0038] As an example, the total amount of electricity for electrochemical oxidation treatment can be any value among 20C / g, 40C / g, 60C / g, 80C / g, 100C / g and 120C / g, or a range between any two values.
[0039] Furthermore, the electrochemical oxidation treatment time is 30 to 60 seconds, which can ensure that the obtained carbon fiber and the matrix resin have a higher interface bonding strength.
[0040] As an example, the time of the electrochemical oxidation treatment can be any value among 30s, 35s, 40s, 45s, 50s, 55s and 60s, or a range between any two of them.
[0041] In some optional embodiments of the present application, the electrochemical oxidation treatment adopts a multi-stage electrochemical oxidation treatment.
[0042] When the total amount of electricity in the electrochemical oxidation treatment is the same, compared with the single-stage electrochemical oxidation treatment, the multi-stage electrochemical oxidation treatment can further improve the interface bonding strength between the prepared carbon fiber and the matrix resin.
[0043] Furthermore, the number of stages of the multi-stage electrochemical oxidation treatment is 2, 3 or 4.
[0044] In some optional embodiments of the present application, the electrolyte for electrochemical oxidation treatment is selected from sodium hydroxide, sodium bicarbonate or sulfuric acid.
[0045] The electrolyte used in the electrochemical oxidation treatment uses the above substances, which can introduce more oxygen-containing functional groups on the surface of the carbon fiber, improve the wettability and adhesion of the carbon fiber, and thus increase the interface bonding strength between the carbon fiber and the matrix resin.
[0046] As an example, sodium hydroxide is selected as the electrolyte for the electrochemical oxidation treatment.
[0047] In some optional embodiments of the present application, the temperature of the carbonization treatment is 1200-1500° C.; the carbon fiber matrix can be fully carbonized, which is beneficial for introducing more oxygen-containing functional groups on the surface of the carbon fiber after subsequent electrochemical oxidation treatment.
[0048] As an example, the temperature of the carbonization treatment may be any value among 1200° C., 1250° C., 1300° C., 1350° C., 1400° C., 1450° C. and 1500° C. or a range between any two values.
[0049] Furthermore, the carbonization treatment time is 40 to 100 seconds, which can fully carbonize the carbon fiber matrix, so as to facilitate the introduction of more oxygen-containing functional groups on the carbon fiber surface after the subsequent electrochemical oxidation treatment.
[0050] As an example, the carbonization treatment time can be any value among 40s, 50s, 60s, 70s, 80s, 90s and 100s, or a range value between any two of them.
[0051] In some optional embodiments of the present application, the method for preparing the intermediate includes: after the electrochemical oxidation treatment, washing and drying the carbon fiber matrix in sequence.
[0052] S120, subjecting the mixed system containing the intermediate and the treatment liquid to ultrasonic treatment.
[0053] In the present application, the treatment liquid contains tannic acid and metal ions. The two adjacent phenolic hydroxyl groups on the benzene ring of tannic acid can coordinate with the metal ions in the treatment liquid in the form of oxygen anions, so that tannic acid and metal ions undergo chelation. Tannic acid has excellent adhesion and can form a coating on the surface of the carbon fiber matrix after simple mixing with metal ions, thereby enhancing the interfacial adhesion between the carbon fiber and the matrix resin. In addition, the tannic acid-metal ion coating can increase the roughness of the carbon fiber surface, generate higher friction between the carbon fiber and the matrix resin, and also enhance the bonding performance of the interface.
[0054] In some optional embodiments of the present application, the metal ions include Fe 3+ 、Na + , Cu 2+ and Zn 2+ At least one of .
[0055] The metal ions are selected from the above ions, which can chelate with tannic acid to increase the roughness of the carbon fiber surface.
[0056] In some optional embodiments of the present application, the solvent in the treatment liquid is water.
[0057] In some optional embodiments of the present application, the pH value of the treatment liquid is 8-9.
[0058] As an example, the pH of the treatment solution may be any value among 8, 8.2, 8.5, 8.7 and 9, or any range between two values.
[0059] In some optional embodiments of the present application, the method for preparing the treatment liquid includes: mixing the tannic acid aqueous solution with the metal salt aqueous solution, and then adjusting the pH to 8-9.
[0060] As an example, the substance used to adjust the pH may be Tris (tromethamine); the metal salt may be at least one of ferric chloride, sodium chloride, copper chloride and zinc chloride.
[0061] In some optional embodiments of the present application, the molar ratio of tannic acid to metal ions is (0.08-0.5):1.
[0062] As an example, the molar ratio of tannic acid to metal ions can be any value among 0.08:1, 0.095:1, 0.1:1, 0.19:1, 0.2:1, 0.25:1, 0.3:1, 0.38:1 and 0.5:1, or a range between any two values.
[0063] Furthermore, the mass concentration of tannic acid in the treatment solution is 0.5-5.0 mg / mL.
[0064] Illustratively, the mass concentration of tannic acid in the treatment liquid can be any value among 0.5 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL, 4 mg / mL, 4.5 mg / mL and 5 mg / mL, or a range between any two of them.
[0065] In some optional embodiments of the present application, the power of the ultrasonic treatment is 120 to 200 W, which can allow the tannic acid-metal ion coating to quickly and fully cover the surface of the carbon fiber matrix, and can allow the prepared carbon fiber to have a higher interface bonding strength with the matrix resin.
[0066] As an example, the power of the ultrasonic treatment can be any value among 120 W, 130 W, 140 W, 150 W, 160 W, 170 W, 180 W, 190 W and 200 W, or a range between any two values.
[0067] Furthermore, the ultrasonic treatment time is 30 to 60 minutes.
[0068] As an example, the time of ultrasonic treatment can be any value among 30 min, 35 min, 40 min, 45 min, 50 min, 55 min and 60 min, or any range between two values.
[0069] Furthermore, in some optional embodiments of the present application, the method for preparing carbon fiber further comprises: after the ultrasonic treatment, drying the carbon fiber after the ultrasonic treatment.
[0070] The present application provides a carbon fiber, which is prepared by using the preparation method provided above.
[0071] The carbon fiber provided in the present application has a high interface bonding strength with the matrix resin, which can improve the interlaminar shear strength of the composite material formed by the carbon fiber and the matrix resin.
[0072] The present application also provides a composite material, comprising a matrix resin and the carbon fiber provided above.
[0073] The composite material provided in the present application has good mechanical properties, the carbon fibers and the matrix resin in the composite material have high interface bonding strength, and the composite material has high interlaminar shear strength.
[0074] It should be noted that the present application does not limit the specific selection of the matrix resin. As an example, the matrix resin can be a thermoplastic resin or a thermosetting resin, for example, the matrix resin can be an epoxy resin.
[0075] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0076] Example 1
[0077] This embodiment provides a method for preparing carbon fiber, and the specific steps are as follows:
[0078] (1) Carbonization treatment:
[0079] The polyacrylonitrile-based carbon fibers were carbonized at 1200°C for 50 seconds.
[0080] (2) Electrochemical oxidation treatment:
[0081] Using sodium hydroxide as electrolyte, the carbon fiber matrix after the carbonization treatment in step (1) is subjected to a second-level electrochemical oxidation treatment; then the carbon fiber matrix after the electrochemical oxidation treatment is washed and dried to obtain an intermediate.
[0082] The amount of electricity for each electrochemical oxidation treatment is 30 C / g, and the time for each electrochemical oxidation treatment is 30 s.
[0083] (3) Ultrasonic treatment:
[0084] The tannic acid aqueous solution and the ferric chloride aqueous solution are mixed and stirred to obtain a mixed solution, and Tris is dissolved in the mixed solution to adjust the pH to 8.5 to obtain a treatment solution. The intermediate obtained in step (2) is immersed in the treatment solution, ultrasonically treated at a power of 120 W for 50 minutes, and then dried to obtain carbon fiber.
[0085] Wherein, in the treatment solution, the mass concentration of tannic acid is 2.0 mg / mL, and the mass concentration of ferric chloride is 1.0 mg / mL.
[0086] Example 2
[0087] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the number of levels of electrochemical oxidation treatment in step (2) is 3, the amount of electricity for each electrochemical oxidation treatment is 20C / g, and the time for each electrochemical oxidation treatment is 20s.
[0088] Example 3
[0089] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the number of levels of electrochemical oxidation treatment in step (2) is 4, the amount of electricity for each electrochemical oxidation treatment is 15C / g, and the time for each electrochemical oxidation treatment is 15s.
[0090] Example 4
[0091] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the amount of electricity used in each stage of electrochemical oxidation treatment in step (2) is 10 C / g.
[0092] Example 5
[0093] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the amount of electricity used in each stage of electrochemical oxidation treatment in step (2) is 50 C / g.
[0094] Example 6
[0095] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the amount of electricity used in each stage of electrochemical oxidation treatment in step (2) is 65 C / g.
[0096] Example 7
[0097] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the amount of electricity used in each stage of electrochemical oxidation treatment in step (2) is 5 C / g.
[0098] Example 8
[0099] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the time for each stage of electrochemical oxidation treatment in step (2) is 15 seconds.
[0100] Example 9
[0101] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the mass concentration of tannic acid in the treatment solution in step (3) is 4.0 mg / mL.
[0102] Example 10
[0103] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the mass concentration of tannic acid in the treatment solution in step (3) is 1.0 mg / mL.
[0104] Embodiment 11
[0105] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the mass concentration of tannic acid in the treatment solution in step (3) is 0.1 mg / mL.
[0106] Example 12
[0107] This embodiment provides a method for preparing carbon fiber. The difference between this embodiment and embodiment 1 is that the power of the ultrasonic treatment in step (3) is 200W.
[0108] Comparative Example 1
[0109] This comparative example provides a method for preparing carbon fiber. The difference between this comparative example and Example 1 is that the electrochemical oxidation treatment and ultrasonic treatment in Example 1 are not performed in this comparative example. The specific steps of this comparative example are as follows:
[0110] The polyacrylonitrile-based carbon fibers were carbonized at 1200°C for 50 seconds.
[0111] Comparative Example 2
[0112] This comparative example provides a method for preparing carbon fiber. The difference between this comparative example and Example 1 is that the electrochemical oxidation treatment in Example 1 is not performed in this comparative example. The specific steps of this comparative example are as follows:
[0113] (1) Carbonization treatment:
[0114] The polyacrylonitrile-based carbon fibers were carbonized at 1200°C for 50 seconds.
[0115] (2) Ultrasonic treatment:
[0116] The tannic acid aqueous solution and the ferric chloride aqueous solution are mixed and stirred to obtain a mixed solution, and Tris is dissolved in the mixed solution to adjust the pH to 8.5 to obtain a treatment solution. The carbon fiber substrate after the carbonization treatment in step (1) is immersed in the treatment solution, ultrasonically treated at a power of 120 W for 50 minutes, and then dried to obtain a carbon fiber.
[0117] Wherein, in the treatment solution, the mass concentration of tannic acid is 2.0 mg / mL, and the mass concentration of ferric chloride is 1.0 mg / mL.
[0118] Comparative Example 3
[0119] This comparative example provides a method for preparing carbon fiber. The difference between this comparative example and Example 1 is that the ultrasonic treatment in Example 1 is not performed in this comparative example. The specific steps of this comparative example are as follows:
[0120] (1) Carbonization treatment:
[0121] The polyacrylonitrile-based carbon fibers were carbonized at 1200°C for 50 seconds.
[0122] (2) Electrochemical oxidation treatment:
[0123] Using sodium hydroxide as electrolyte, the carbon fiber matrix after the carbonization treatment in step (1) is subjected to a second-level electrochemical oxidation treatment; then the carbon fiber matrix after the electrochemical oxidation treatment is washed and dried to obtain carbon fiber.
[0124] The amount of electricity for each electrochemical oxidation treatment is 30 C / g, and the time for each electrochemical oxidation treatment is 30 s.
[0125] Experimental example
[0126] The water contact angle of the carbon fibers prepared in Examples 1 to 12 and Comparative Examples 1 to 3 was tested using the meniscus method; the carbon fibers prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were prepared into composite materials, and the interlaminar shear strength (ILSS) of the composite materials was measured according to GB / T1450.1; the test results are shown in Table 1.
[0127] The preparation method of the composite material is as follows: the carbon fiber is wound and fixed; AG80 epoxy resin and 4,4'-diaminodiphenyl sulfone (curing agent) are mixed and coated on the carbon fiber, and the composite material is obtained after drying.
[0128] Table 1
[0129]
[0130]
[0131] It can be seen from Table 1 that the interlaminar shear strength of the composite materials formed by the carbon fiber and the resin obtained in Examples 1 to 12 is significantly higher than the interlaminar shear strength of the composite materials formed by the carbon fiber and the resin obtained in Comparative Examples 1 to 3, indicating that the carbonization treatment, the electrochemical oxidation treatment and the ultrasonic treatment in the "tannic acid-metal ion treatment solution" in sequence can make the obtained carbon fiber and the resin have a higher interface bonding strength.
[0132] From the comparison of Examples 1 to 3, it can be seen that when the total amount of electricity in the electrochemical oxidation treatment is the same, as the number of stages of the electrochemical oxidation treatment increases, the interlaminar shear strength of the composite material also increases.
[0133] From the comparison between Example 1 and Examples 4 to 7, it can be seen that when the number of electrochemical oxidation treatments is the same, the total amount of electricity for the electrochemical oxidation treatment will further affect the interlaminar shear strength of the composite material formed by the carbon fiber and the resin.
[0134] From the comparison between Example 1 and Example 8, it can be seen that when the number of electrochemical oxidation treatments and the total amount of electricity are consistent, the time of each electrochemical oxidation treatment has little effect on the interlaminar shear strength of the composite material formed by carbon fiber and resin.
[0135] From the comparison between Example 1 and Examples 9 to 11, it can be seen that as the mass concentration of tannic acid in the treatment solution increases during the ultrasonic treatment, the interlaminar shear strength of the composite material also increases.
[0136] From the comparison between Example 1 and Example 12, it can be seen that the ultrasonic power of the ultrasonic treatment will further affect the interlaminar shear strength of the composite material formed by the carbon fiber and the resin.
[0137] In summary, the present application sequentially performs carbonization treatment and electrochemical oxidation treatment on the carbon fiber matrix, so that more oxygen-containing functional groups can be introduced into the carbon fiber surface, which can improve the wettability and adhesion of the carbon fiber, so as to improve the interface bonding strength between the carbon fiber and the matrix resin. Furthermore, the present application performs ultrasonic treatment on the carbon fiber matrix after electrochemical oxidation treatment in a system containing tannic acid and metal ions, which can further improve the interface bonding strength between the obtained carbon fiber and the matrix resin.
[0138] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A method for preparing carbon fiber, characterized in that: include: The carbon fiber matrix after the carbonization treatment is subjected to electrochemical oxidation treatment to obtain an intermediate; subjecting the mixed system containing the intermediate and the treatment liquid to ultrasonic treatment; Wherein, the treatment liquid contains tannic acid and metal ions.
2. The preparation method according to claim 1, characterized in that: The total amount of electricity for the electrochemical oxidation treatment is 20 to 120 C / g; Optionally, the electrochemical oxidation treatment time is 30 to 60 seconds.
3. The preparation method according to claim 1, characterized in that: The electrochemical oxidation treatment adopts multi-stage electrochemical oxidation treatment; Optionally, the number of stages of the multi-stage electrochemical oxidation treatment is 2, 3 or 4.
4. The preparation method according to claim 1, characterized in that: The electrolyte for the electrochemical oxidation treatment is selected from sodium hydroxide, sodium bicarbonate or sulfuric acid.
5. The preparation method according to claim 1, characterized in that: The temperature of the carbonization treatment is 1200-1500°C; Optionally, the carbonization treatment time is 40 to 100 seconds.
6. The preparation method according to any one of claims 1 to 5, characterized in that The metal ions include Fe 3+ 、Na + , Cu 2+ and Zn 2+ At least one of; Or / and, the solvent in the treatment liquid is water; Or / and, the pH of the treatment liquid is 8-9.
7. The preparation method according to any one of claims 1 to 5, characterized in that The molar ratio of the tannic acid to the metal ion is (0.08-0.5):1; Optionally, the mass concentration of the tannic acid in the treatment liquid is 0.5 to 5.0 mg / mL.
8. The preparation method according to any one of claims 1 to 5, characterized in that The power of the ultrasonic treatment is 120 to 200 W; Optionally, the ultrasonic treatment time is 30 to 60 minutes.
9. A carbon fiber, characterized in that: The carbon fiber is prepared by the preparation method according to any one of claims 1 to 8.
10. A composite material, characterized in that: The method comprises a matrix resin and the carbon fiber as claimed in claim 9.
Citation Information
Patent Citations
Method for electrochemically modifying surface of ultrasonic-enhanced carbon fiber
CN103321036A
Carbon-fiber surface modification method
CN107034662A
Method for grafting branched molecule tannic acid on surface of carbon fiber
CN107761375A
Preparation method for tannic acid modified ultrahigh molecular weight polyethylene fibers and composite material thereof
CN108395675A
Surface treatment method of carbon fiber and carbon fiber
CN117512981A
